2019
DOI: 10.1177/0363546518817527
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Autograft Transplantation Technique Augmented by an Ultrapurified Alginate Gel Enhances Osteochondral Repair in a Rabbit Model

Abstract: Background: One of the most important limitations of osteochondral autograft transplantation (OAT) is the adverse effect on donor sites in the knee. To decrease the number and/or size of osteochondral defects, we devised a method with biomaterial implantation after OAT. Hypothesis: OAT augmented by ultrapurified alginate (UPAL) gel enhances cartilage repair capacity. Study Design: Controlled laboratory study. Methods: Seventy-five osteochondral defects in rabbits were divided into 3 groups: osteochondral defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…19,40 The low endotoxin level enables safe clinical application of the UPAL gel because it does not induce immunologic reactions to the implanted material. 11,14 The current clinical and radiographic findings suggested that no infections or allergic reactions occurred in any of the 5 patients. Additionally, second-look arthroscopy and biopsy provided visual confirmation that there were no adverse effects derived from the material in the soft tissues of the elbow joint and cartilage, thereby indicating a reasonable safety profile.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…19,40 The low endotoxin level enables safe clinical application of the UPAL gel because it does not induce immunologic reactions to the implanted material. 11,14 The current clinical and radiographic findings suggested that no infections or allergic reactions occurred in any of the 5 patients. Additionally, second-look arthroscopy and biopsy provided visual confirmation that there were no adverse effects derived from the material in the soft tissues of the elbow joint and cartilage, thereby indicating a reasonable safety profile.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have demonstrated that UPAL gel administration without exogenous cell implantation induces hyaline-like cartilage repair, possibly because this hydrogel retains migrated cells and enhances cellular proliferation and chondrogenic differentiation. 2,11 Using a canine model, Baba et al 1 Recent studies have demonstrated that mosaicplasty provides favorable clinical outcomes in patients with large capitellar OCD lesions. 16,17 Mosaicplasty is based on the concept that osteochondral grafts harvested from the articular cartilage of the knee joint provide an adequate biomechanical environment and friction pattern similar to that of the normal elbow joint.…”
Section: Discussionmentioning
confidence: 99%
“…UPAL gel (Sea Matrix; Mochida Pharmaceutical Co) with a molecular weight of 1700 kDa, as reported previously, was used in this experiment. 12 Generally, edible alginate is made from natural kelp, which has some impurities such as endotoxin that could cause a xenobiotic reaction. To prevent this, the endotoxin level of UPAL gel has been reduced to a sufficiently low level (5.76 EU/g), which passes the biological safety test for implantation in vivo.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Hydrogels are well adapted for cartilage repair as they have high water contents mimicking cartilage-based ECM glycosaminoglycans [ 86 ] and biocompatibility, often with lower mechanical properties compared with solid scaffolds [ 87 , 88 ]. Natural polymer biomaterials such as collagen [ 89 ], alginate [ 90 ], gellan gum [ 91 ], or silk fibroin [ 92 ] have been studied as scaffolds for cartilage repair due to their biocompatible nature promoting proliferation and differentiation of the encapsulated cells which makes them promising systems in various tissue engineering approaches [ 74 , 92 , 93 ]. Solid scaffolds are highly porous structures, allowing for migration and infiltration of cells from the surrounding tissue.…”
Section: Scaffolds For Osteochondral Repairmentioning
confidence: 99%